Applied utility and the auto-ethnographic short story: persuasions for, and illustrations of, writing critical social science - Gilbourne, David; Jones, Robyn; Jordan, Spencer (Taylor & Francis, 2014)
In some quarters it is argued that, narrative researchers might be classified as being either storyanalysts or storytellers. They go on to suggest that one feature of storytellers is that they undertake a form of analysis as the process of writing unfolds. With these sentiments in mind, in the present paper, we consider how auto-ethnographical accounts of traumatic and challenging life events might, through the analysis contained within, demonstrate value within the realm of applied pedagogy. In making our case we embrace and adapt the literary genre of storytelling, more specifically, the short story. The story presented here, ‘Travel Writer’, offers an opaque, multicontextualised and lifelong view of career transition. The present paper, in more general terms, considers the capacity of auto-ethnography and, more specifically, the short storied version of it, to engender critical reader engagement, to encourage personal reflection in others, and to act as a point of stimulus for the enactment of applied debate through the lens of critical social science. With regards to the assumptions of critical social science, the final discussion also considers how the auto-ethnographic text, as a pedagogic tool, might help others to contest and challenge the meta-narratives that, we argue, risk stagnating established thinking.